Gut microbial change after administration of Lacticaseibacillus paracasei AO356 is associated with anti-obesity in a mouse model - Song, Eun-Ji; Lee, Eun-Sook; Kim, Young In; Shin, Dong-Uk; Eom, Ji-Eun; Shin, Hee Soon; Lee, So-Young; Nam, Young-Do (Frontiers in Endocrinology, 2023)
The status of an impaired gut microbial community, known as dysbiosis, is associated with metabolic diseases such as obesity and insulin resistance. The use of probiotics has been considered an effective approach for the treatment and prevention of obesity and related gut microbial dysbiosis. The anti-obesity effect of Lacticaseibacillus paracasei AO356 was recently reported. However, the effect of L. paracasei AO356 on the gut microbiota has not yet been identified. This study aimed to elucidate the effect of L. paracasei AO356 on gut microbiota and ensure its safety for use as a probiotic.Methods: Oral administration of L. paracasei AO356 (10 7 colony-forming units [CFU]/mg per day, 5 days a week, for 10 weeks) to mice fed a high-fat diet significantly suppressed weight gain and fat mass. We investigated the composition of gut microbiota and explored its association with obesity-related markers.Results: Oral administration of L. paracasei AO356 significantly changed the gut microbiota and modified the relative abundance of Lactobacillus, Bacteroides, and Oscillospira.Bacteroides and Oscillospira were significantly related to the lipid metabolism pathway and Effects of Lacticaseibacillus paracasei AO356 on gut microbiota 2 obesity-related markers. We also confirmed the safety of L. paracasei AO356 using antibiotics resistance, hemolysis activity, bile salt hydrolase activity, lactate production, and toxicity tests following the safety assessment guidelines of the Ministry of Food and Drug Safety (MFDS).Discussion: This study demonstrated that L. paracasei AO356 is not only associated with an anti-obesity effect but also with changes in the gut microbiota and metabolic pathways related to obesity. Furthermore, the overall safety assessment seen in this study could increase the potential use of new probiotic materials with anti-obesity effects.